Webster's NewWorld Dictionary Of Synonyms - Ruth Kimball Kent (Prentice Hall Press, 1984)
a guide to synonyms, words with nearly the same meaning ,and also to antonyms,words with an opposite meaning,arranged in concise paragraph to show the subtle differences